Babylonian Physiognomic Omens in Cryptic Hebrew Orthography - Geller, M. J. (Aestimatio, 2023)
A unique text of physiognomic omens in Hebrew from the Dead Sea Scrolls (4Q186) is remarkable in that it mimics the similar Akkadian omens upon which it is based, in that it is written in a left-to-right format beginning with the column on the left. The Qumran text also avoids final letters and includes some words in Paleo-Hebrew script and Greek letters, all pointing to its Vorlage being an exemplar of Graeco-Babyloniaca (an Akkadian text in Greek transliteration), employed in order to make technical Akkadian more widely accessible.